Competing discourses of the “Maya Past” (Revista de Estudos e Pesquisas sobre as Américas, 2010)
The use of the "Maya past" for tourism marketing purposes has been a successful tool for attracting international visitors to Mexico for decades. Images of the Maya zone emerge, in part, from an academic focus on the "Maya past" that includes curiosity about the so-called "collapse" of the Classic Maya civilization. The Ancient Maya are seen as “mysterious" and their society as "enigmatic". But the voices of the almost thirty million Maya people who live in Mexico and Guatemala are only vaguely heard in the discourses of tourism and of academia. This paper examines three competing discourses of the Maya and proposes that these discourses represent epistemologies that are nested in relationships of power, such that the Maya discourse is silenced. As such, the dominant discourses of the Maya past can undermine the Maya understanding of their own past, and become a self-fulfilling prophecy regarding the “collapse” of the contemporary Maya.